The synthesis and Co(II), Co(III), Cu(II) and Ni(II) complexes of a new symmetrical vic-dioxime - Cukurovali, A; Tas, E; Kaya, M (Marcel Dekker Inc, 1998)
9,10-Bis(hydroxyimino)-4,8,11,15-tetraaza-1,2,17,18-O-di-iso-butylideneoctadecane (LH2), has been synthesized starting from 1,2-O-iso-butylidene-4-aza-7-aminoheptane, which has been prepared from the 1-bromo-2,3-O-iso-butylidenepropane and dichloroglyoxime. The structure of this vic-dioxime has been determined as the (E,Z)-form according to H-1 NMR, C-13 NMR and IR data. Mononuclear complexes having a metal-ligand ratio of 1:2 have been prepared with Co(II), Cu(II), Ni(II). In addition, a Co(III)(py)Cl complex of the ligand was prepared with pyridine (py) and chloride ion as axial ligands. Structures of the ligand and its complexes are proposed based on elemental analyses, IR, C-13 and H-1 NMR spectra, magnetic susceptibility measurements, thermogravimetric analyses (TGA) and differential thermal analyses (DTA).
Keywords: Palladium(Ii); Copper(Ii); Nickel(Ii); Cobalt(Ii); (E,E)-Dioximes; Mononuclear; Uranyl(Vi)